Mindfulness and mental health in medical staff in the COVID-19 period: Mediating role of perceived social support and sense of security. Issue 5 (3rd September 2022) - Liao, Jundong; Sun, Xinlong; Mai, Xiaohao; Du, Yuhui; Li, Fang
Abstract : This study examined the association between mindfulness and the mental health outcomes of medical staff during the COVID-19 outbreak period. We also explored the perceived social support and sense of security as mediators in this relationship. The participants were 400 medical staff (male= 23%, female= 77%; 14.8% with suspected exposure to COVID-19) from China. The medical staff completed the Mindful Attention Awareness Scale (MAAS), Perceived Social Support Scale (SSS), Security Questionnaire (SQ), Self-Rating Depression Scale (SDS), and General Well-being Scale (GWB). The path analysis results showed that mindfulness was associated with lower depression symptoms and higher subjective well-being. The medical staffwho perceived higher social support and s sense of security had lower mental distress and higher well-being. Perceived social support enhanced mental health and well-being through the sense of security. The predictive effect of perceived social support on the sense of security of medical staff who had contact with suspected COVID-19 patients was significantly stronger than that of medical staff did not have suspected COVID-19 contact. These findings indicate a need to provide more mindfulness-related training (e.g., Mindfulness-Based Stress Reduction, MBSR) to improve the mental health of medical staff and provide more support to ensure their sense of security. In addition, more humanistic care and material resources should be provided to medical staff in high-risk departments.